2012
DOI: 10.2478/v10184-011-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Classification of mesic grasslands and their transitions of South Transdanubia (Hungary)

Abstract: -Relevés from meadows and pastures of South Transdanubia (Hungary) are evaluated by clustering and ordination methods. The relevé selection focused on the Arrhenatheretalia order but its transitions towards other types were also included. The groups of relevés are delimited and described according to differential, dominant and constant species. Ecological conditions of the groups were compared using indicator values. Nine groups were distinguished, four of them belonging strictly to the order Arrhenatheretalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…), as also pointed out by Lengyel et al. (). The species composition and DCA analysis suggest that these grasslands should be classified within the alliance Arrhenatherion elatioris .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…), as also pointed out by Lengyel et al. (). The species composition and DCA analysis suggest that these grasslands should be classified within the alliance Arrhenatherion elatioris .…”
Section: Discussionsupporting
confidence: 75%
“…In our analysis, these stands (together with some wet Arrhenatherion elatioris stands) are separated as a single cluster with a transitional position between Cluster 5 and 10 in the DCA diagram (Fig. 2), as also pointed out by Lengyel et al (2012). The species composition and DCA analysis suggest that these grasslands should be classified within the alliance Arrhenatherion elatioris.…”
Section: Discussionsupporting
confidence: 74%
“…Worthy noticing is the fact that within green areas fresh meadows are the most abundant floristically not only within our country (LenGyeL et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Unweighted mean Ellenberg indicator values (EIVs hereafter) for light availability (L), temperature (T), soil moisture (W), soil reaction (R), and nutrient availability (N) were calculated for each plot using the system of Borhidi (1995). A number of studies have demonstrated that, despite the ordinal nature of EIVs, mean EIVs provide reliable estimates of the environmental conditions of an area (Lengyel et al, 2012;Tölgyesi et al, 2014); therefore, they are useful for monitoring environmental changes. We used one-way analysis of similarities (ANO-SIM) to compare the species composition of plots among the forest age classes, applying the Jaccard dissimilarity and 9999 permutations.…”
Section: Statistical Analysesmentioning
confidence: 99%